2015
DOI: 10.1111/jcmm.12723
|View full text |Cite
|
Sign up to set email alerts
|

Role of stem cells during diabetic liver injury

Abstract: Diabetes mellitus is one of the most severe endocrine metabolic disorders in the world that has serious medical consequences with substantial impacts on the quality of life. Type 2 diabetes is one of the main causes of diabetic liver diseases with the most common being non‐alcoholic fatty liver disease. Several factors that may explain the mechanisms related to pathological and functional changes of diabetic liver injury include: insulin resistance, oxidative stress and endoplasmic reticulum stress. The realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
(103 reference statements)
1
14
0
Order By: Relevance
“…In clinical settings, the level of ketone bodies increases significantly under several pathological circumstance such as diabetes . Interestingly, it has been reported that diabetic patients have a higher incidence of liver disease, and the elevation of ketone bodies has been regarded as a harmful factor in diabetes‐associated liver injury . In agree with this opinion, the present study found that supplementation with BHB exacerbated LPS/ d ‐Gal‐induced liver injury.…”
Section: Discussionsupporting
confidence: 86%
“…In clinical settings, the level of ketone bodies increases significantly under several pathological circumstance such as diabetes . Interestingly, it has been reported that diabetic patients have a higher incidence of liver disease, and the elevation of ketone bodies has been regarded as a harmful factor in diabetes‐associated liver injury . In agree with this opinion, the present study found that supplementation with BHB exacerbated LPS/ d ‐Gal‐induced liver injury.…”
Section: Discussionsupporting
confidence: 86%
“…MSCs have the ability to induce endogenous stem cells to regenerate, they promote HOCs (hepatic oval cells) which considered as facultative progenitor cells in the liver. They have the potential to trans-differentiate into fully functional mature hepatic cells [28]. MSCs have indirect mechanism in treated diabetic liver injury by reducing hyperglycemia as it directly differentiate into islet beta cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the issues addressed in this review (OS and inflammation), Li et al [ 133 ] and Shields et al [ 134 ] described the typical change in microcirculation that occurs in diabetic patients after liver surgery. The ischaemic period and liver perfusion recovery are important factors related to hepatocellular damage because microcirculatory collapse is followed by a pronounced reduction of tissue oxygenation [ 135 ], which might result in degeneration and necrosis of hepatocytes and consequent liver dysfunction [ 136 ]. Experimental models of I/R injury have offered evidence that insufficient hepatic microcirculatory perfusion, inflammatory cell activation, and consequent generation of ROS, cytokines, and chemokines can be considered essential in I/R syndrome [ 137 ].…”
Section: Diabetes Mellitus In Clinical Situationsmentioning
confidence: 99%